The Health Sector in Ghana : A Comprehensive Assessment - Saleh, Karima (Washington, DC: World Bank, 2013)
Ghana has committed politically, legislatively, and fiscally to providing universal health insurance coverage for its population with the intent of reducing financial barriers to utilization of health care.. However, under current cost and enrollment projections the system will not be financially sustainable in the long term, so there is more work to do. This book provides an important evidence-based review of the current performance of Ghana's health system and options for reform. As such, it provides an overall picture of the Ghana health sector, how things were and how things have changed, as well as a situational analysis of the performance of the health delivery and health financing systems using the latest available data. Finally, it discusses key reform issues and options in the context of the country's likely fiscal space. An important and valuable contribution of this book is its examination of how Ghana is performing compared to its neighboring countries and compared to other countries with similar incomes and health spending, providing global benchmarks for Ghana's health system performance.